Polypropylene and polypropylene/polyglecaprone (Ultrapro(r)) meshes in the repair of incisional hernia in rats - Utiyama,Edivaldo Massazo (2015)
PURPOSE: To compare the inflammatory response of three different meshes on abdominal hernia repair in an experimental model of incisional hernia.METHODS: Median fascial incision and skin synthesis was performed on 30 Wistar rats. After 21 days, abdominal hernia developed was corrected as follows: 1) No mesh; 2) Polypropylene mesh; and, 3) Ultrapro(r) mesh. After 21 days, the mesh and surrounding tissue were submitted to macroscopic (presence of adhesions, mesh retraction), microscopic analysis to identify and quantify the inflammatory and fibrotic response using a score based on a predefined scale of 0-3 degrees, evaluating infiltration of macrophages, giant cells, neutrophils and lymphocytes.RESULTS: No significant difference was seen among groups in adherences, fibrosis, giant cells, macrophages, neutrophils or lymphocytes (p>0.05). Mesh shrinkage was observed in all groups, but also no difference was observed between polypropylene and Ultrapro mesh (7.0±9.9 vs. 7.4±10.1, respectively, p=0.967). Post-operatory complications included fistula, abscess, dehiscence, serohematic collection and reherniation, but with no difference among groups (p=0.363).CONCLUSION:There is no difference between polypropylene (high-density) and Ultrapro(r) (low-density) meshes at 21 days after surgery in extraperitoneal use in rats, comparing inflammatory response, mesh shortening, adhesions or complications.